Jornalismo, literatura e engajamento: direcionando o olhar para as estratégias discursivas praticadas pelo jornal Folha de S.Paulo, durante a cobertura da Campanha Diretas Já - Jesus, Rosane Martins de (2011)
Considering Kovach and Rosenstiel (2004) for whom the journalists must supply information by an attractive and involving writing, this research reflects on the aproximant discursive strategies used for the periodical Folha de S. Paulo, during the covering of the Campaign for the Diretas Já. Having as metodological reference the analysis of the speech, of Freench tradition, 88 news articles of the editorial of politics of the Folha de S. Paulo, published between 13/01/1984 and 26/04/1984, was analized. With this research, it was objectified, specifically: to identify the use of the aproximant discursive strategies during the covering; to know how these strategies helped to arouse the interest for the thematic, popularizing the Campaign and finally, to verify as the choice for these strategies had helped to establish complicity ties between the periodical and its reader, during the Diretas Já. At the end of the analysis, it was inferred, amongst other results, that: Folha de S.Paulo prioritized the new articles written under a literary perpective; the sentimentality was emphasized in practically all the new articles analyzed; the explicit presence of the reporter in the texts helped to construct to a complicity ties between the readers and the Folha; and the prominence given to histories of life of common people, most of them living of the peripheries of the big cities, contributed so that the citizen-common recognized himself as an active participant in the Campaign. It was also concluded, also, that the use of the discursive strategies had contributed to stimulate the participation of the Brazilian society contributing to the mobilization was adopted as a popular manifestation and not politics only.